Coping strategies and posttraumatic growth following transient ischemic attack: a qualitative study - Kindermann, David; Grosse-Holz, Veronika Maria; Andermann, Martin; Ringleb, Peter A.; Friederich, Hans-Christoph; Rizos, Timolaos; Nikendei, Christoph (Journal of Clinical Medicine, 2023)
A transient ischemic attack (TIA) is defined as a temporary neurological dysfunction due to focal brain ischemia. We aimed to identify common coping strategies and the possible occurrence of posttraumatic growth in TIA patients. Semistructured interviews were conducted with TIA patients three months after TIA. We asked the participants about possible changes in the aftermath of their TIA and their way of coping with said changes. All interviews were tape-recorded and subsequently transcribed verbatim. Thematic content analysis was performed to identify main categories and themes. Seventeen patients with a median age of 66 years completed the semistructured interviews. Qualitative content analysis revealed 332 single codes, from which the three main categories “impairments as a consequence of TIA”, “coping strategies” and “posttraumatic growth” were generated. The main categories were further subdivided into seven categories and thirty-six themes. TIA patients may suffer from various physical impairments, which also involve medication side effects. Activating resources on the one hand, and avoiding negative thoughts and feelings on the other hand, were identified to be the relevant coping strategies in TIA patients. Posttraumatic growth seems to be a common phenomenon after TIA, which may have important implications for treatment and rehabilitation.